Randomized clinical trial of single‐incision versus multiport laparoscopic colectomy. Issue 10 (10th August 2016) - Watanabe, J.; Ota, M.; Fujii, S.; Suwa, H.; Ishibe, A.; Endo, I.
Abstract: Background: The efficacy and safety of single‐incision laparoscopic colectomy (SILC) for colonic cancer remain unclear. The aim of this study was to determine the outcomes of SILC compared with multiport laparoscopic colectomy (MPLC) for colonic cancer. Methods: Patients with histologically proven colonic carcinoma located in the caecum, ascending, sigmoid or rectosigmoid colon, clinically diagnosed as stage 0–III by CT, were eligible for this study. Patients were randomized before surgery and underwent tumour dissection with complete mesocolic excision. Safety analyses were conducted according to randomization groups. Results: A total of 200 patients were enrolled and randomized to the MPLC (100 patients) or SILC (100 patients) arm. Surgical outcomes were similar between the MPLC and SILC arms, including duration of operation (mean 162 versus 156 min respectively; P = 0·273), blood loss (mean 8·8 versus 21·4 ml; P = 0·102), conversion to open laparotomy (2·0 versus 1·0 per cent; P = 0·561), reoperation (3·0 versus 3·0 per cent; P = 1·000), time to first flatus (both median 1 day; P = 0·155) and postoperative hospital stay (both median 6; P = 0·372). The total skin incision length was significantly shorter in the SILC arm (mean 4·4 cm versus 6·8 cm in the MPLC arm; P < 0·001). The median duration of analgesia use was 5 days in the MPLC and 4 days in the SILC arm ( P = 0·485). Overall complication rates were equivalent (15·0 versus 12·0 per cent respecitvely; P = 0·680). Conclusion: SILC is not superior to MPLC. Registration number: UMIN000007220 (http://www.umin.ac.jp/ctr/index.htm ). Abstract : No advantage